Analysis of Soybean Raw Material Inventory Control for Production Sustainability at a Tofu Factory in Padang Cermin District, Pesawaran Regency - Farhan, Taufiq; Purnomo, Agus (Indonesian Journal Publisher, 2025)
This study explores raw material inventory management at Bu Supi Tofu Factory in Padang Cermin, focusing on the Economic Order Quantity (EOQ) method to address challenges in soybean procurement. The factory uses a traditional purchasing system, leading to overstocking, increased costs, and reduced product quality. Through a qualitative-descriptive approach, the research evaluates the factory's current practices, calculates the optimal order quantity using the EOQ model, and compares it with the existing system. The results indicate that implementing EOQ can reduce ordering costs, storage expenses, and surplus stock while maintaining product quality and enhancing operational efficiency. This study highlights the potential benefits of applying modern inventory management techniques in small-scale industries to optimize resources and improve profitability.